"Been Down So Long It Looks Like Up to Me": Rethinking the Humanities (in Times of) Crisis. Issue 3 (4th May 2019) - De Chavez, Jeremy; Varadharajan, Asha
ABSTRACT: This essay reflects on the connection between the Humanities and democracy with the aim of formulating an alternative critique that does not confuse democracy with nor concedes it to oligarchy, that does not exclusively reside in academic culture, and that does not elide cultural difference and translation. While agreeing with Martha Nussbaum that there should be strong ties between humanistic inquiry and democratic sensibilities, this essay conceives of that relationship differently: not (Nussbaum's) "democracy needs the Humanities" but rather the Humanities need democracy. Toward that goal, the essay rethinks cultural critique alongside Jacques Rancière's radical vision of democratic equality and interprets an image by photojournalist Raffy Lerma that reframes Philippine president Rodrigo Duterte's war on drugs. Lerma's photograph serves as a litmus test for the protocols of reading as well as a limit-case forcing both democracy and the Humanities to revisit their vaunted capacity, in Nussbaum's terms, to cultivate the imagination, enrich meaning, and educate for global citizenship.